If Lacan, then Althusser: From evident affinity to theoretical homology - López-Ríos, Luis Pablo (2025)
This paper presents a preliminary outline concerning the possible homological relationship between Althusser and Lacan. First, it examines the affinities between both thinkers: their returns to Freud and Marx, as well as their critique of psychologism and humanism. After considering their evident discrepancies, a homological theoretical reasoning is identified at the level of enunciation of both theorists: the logic of structural causality. The article concludes with a reassessment of the event as a condition of the structure, and with the proposal of a logical articulation between Althusser and Lacan for a critique of capitalist structure.